The problem between the event and the time for the ancients and the modernists (Journal of the College of Basic Education, 2022)
Praise be to God who taught by the pen, and I pray and greet the master of the two races, Abi Al-Qasim, may God’s blessings and peace be upon him and his family and companions.There are many issues in Arabic grammar that still need to be studied in depth. In order to obtain scientific answers that solve its problems, and from these issues (was), it was problematic for grammarians to call it (the incomplete).And based on this problem, the topic of our research came (the problem between the event and the time of the ancients and the modernists), in which we discussed the truth, the naqih.